Empowerment Strategies for Creative Industry MSMEs to Increase Competitiveness in the Digital Era in the Wood Processing Industry South Tangerang City - Aidil Amin Effendy; Azhar Affandi; Umi Narimawati; Sidik Priadana; Iman Sudirman; Horas Djulius (International Journal of Social Sciences, 2026)
This study aims to analyze the Empowerment Strategy of Creative Industry MSMEs to Increase Competitiveness in the Digital Era in the Wood Processing Industry in South Tangerang City. This research method uses qualitative methods, gaining an in-depth understanding of data collection techniques through observation, documentation, and interviews. Semi-structured interviews based on a predetermined interview guide were conducted with several informants from creative industry MSMEs in South Tangerang City, the MSME Association, KADIN (Indonesian Chamber of Commerce and Industry) in the South Tangerang region, the South Tangerang MSME and Cooperative Office, and expert judgment from academics and experts in their fields. The analysis of the interviews indicates that the empowerment of e-commerce-based creative industry MSMEs in the wood processing sector in South Tangerang is still suboptimal, as evidenced by minimal government support, limited capital, limited digital marketing, and various operational constraints such as product quality, raw materials, and machine breakdowns. Although some MSMEs are able to retain customers through quality service, their overall competitiveness remains low due to technological limitations and market changes. A SWOT analysis revealed that MSMEs possess strengths in product quality and customer relationships, as well as opportunities from the growing digital market. However, they still face the threat of competition and fluctuating raw material prices. Therefore, the SWOT strategy emphasizes the need to maximize strengths and opportunities while addressing weaknesses and threats to increase MSME competitiveness in the digital era.